Scoping Review: Analisis Vasektomi sebagai Faktor Risiko Disfungsi Seksual pada Pria - Andini Salsabila Puteri; Eka Nurhayati; Bambang Setiohadji (Bandung Conference Series: Medical Science, 2024)
Abstract. Vasectomy is a male sterilization procedure to prevent pregnancy by cutting the vas deferens therefore it will block sperm from reaching the semen that is ejaculated from the penis. People rarely choose vasectomy as a contraceptive method of choice because of concerns that vasectomy can cause sexual dysfunction. This research aims to analyze vasectomy as a factor of sexual dysfunction in men. This research used a scoping review study to identify and analyze articles through database sources such as ScienceDirect, PubMed, and Taylor and Francis, specific journals such as European Urology, Urology, The European Journal of Contraception & Reproductive Health Care, and The Journal of Sexual Medicine, and Grey Literature published in 1994-2023. This research used The PRISMA diagram method and resulted in seven articles that met the inclusion and eligibility criteria. Based on the results from the analysis of seven articles, two articles concluded that there was an increase in sexual function after vasectomy because there was no anxiety about the pregnancy after sexual intercourse, one article concluded that there was a decrease in sexual function in men who were forced to have vasectomy by their partner’s and resulted in an increase in work of sympathetic nerve that can interfere the sexual function, and four articles concluded that there was no effect of vasectomy on sexual function. Abstrak. Vasektomi merupakan prosedur sterilisasi pada pria dengan tujuan untuk mencegah kehamilan yang dilakukan dengan mengikat dan memotong saluran vas deferens agar sperma tidak dapat bercampur dan keluar bersama semen. Masyarakat masih jarang memilih vasektomi sebagai metode kontrasepsi pilihan disebabkan karena kekhawatiran bahwa vasektomi dapat menyebabkan disfungsi seksual. Tujuan dari penelitian ini yaitu untuk menganalisis vasektomi sebagai faktor risiko disfungsi seksual pada pria. Penelitian menggunakan studi scoping review untuk mengidentifikasi dan menganalisis artikel melalui sumber database seperti ScienceDirect, PubMed, dan Taylor and Francis, jurnal spesifik seperti European Urology, Urology, The European Journal of Contraception & Reproductive Health Care, dan The Journal of Sexual Medicine, serta Grey Literature yang diterbitkan pada tahun 1994-2023. Metode diagram PRISMA digunakan dalam penelitian ini dan menghasilkan tujuh artikel yang memenuhi kriteria inklusi dan kelayakan. Berdasarkan hasil analisis dari tujuh artikel, dua artikel menyimpulkan bahwa terdapat peningkatan fungsi seksual pascavasektomi karena tidak adanya kecemasan akan hamilnya pasangan apabila melakukan hubungan seksual, satu artikel menyimpulkan bahwa terdapat penurunan fungsi seksual pada pria yang terpaksa melakukan vasektomi karena tuntutan pasangan dan berakibat pada peningkatan kerja saraf simpatis yang dapat mengganggu fungsi seksual, dan empat artikel menyimpulkan bahwa tidak ada pengaruh vasektomi terhadap fungsi seksual.